Influence of flood pulse on ecological aspects of an iliophagous fish from Eastern Eastern Amazonia, Brazil - Ayres-Santos, Bruno; Freitas, Tiago Magalhães da Silva; Montag, Luciano Fogaça de Assis (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
The aim of this study was to describe ecological aspects of the iliophagous fish Cyphocharax abramoides, in Eastern Amazonia, Brazil, concerning the variation of organic carbon content (OCC) in ingested food, growth pattern, and condition factor (K). The OCC present in stomach contents was obtained bimonthly and evaluated with a Kruskal-Wallis test. The growth pattern was obtained through the length-weight relationship. Bimonthly K variation was also assessed with a Kruskal-Wallis test. Our results showed differences in OCC values during the studied period, with lower OCC values in the dry period and the highest OCC values during the flooding. The growth pattern was established as positive allometric growth (b > 3). K values also differed within the sampling periods, which showed different periods of physiological activity. The results also suggest that changes in these parameters can be associated with physical changes of the aquatic environment due to the flood pulse. Ecological studies can increase our knowledge about the relationship between species and environment, and are relevant in a still poorly documented region of high species richness such as the Amazon.